IDENTIFICATION OF BAINITE IN A MULTI-PHASE MICROSTRUCTURE OF AN AUSTEMPERED STEEL ALLOY: A METALLOGRAPHY APPROACH - Muhammad Yunan Hasbi; M R Wida'atullah; Fatayalkadri Citrawati; Septian Adi Chandra; L. Suhaemi (Jurnal Sains Materi Indonesia, 2021)
IDENTIFICATION OF BAINITE IN A MULTI-PHASE MICROSTRUCTURE OF AN AUSTEMPERED STEEL ALLOY: A METALLOGRAPHY APPROACH. Structural characterization of a multi-phase steel has become an exciting issue in various studies to date. This relates to the difficulty in distinguishing phases with similar morphology, i.e. bainite and martensite, through chemical etching. This study discusses a method to observe bainite phase through a metallographic approach on FeNi steel using color etching. Variations in the use of etching in this research include 2% nital, 4% picral, and 15% sodium metabisulphite (SMB). First, the samples were austenized then austempered at either 400 °C or 500 °C, for 60 min followed by quenching in either water or brine solution. Based on optical microscope observations, SMB color etching provides more explicit information on the visualization of bainite and martensite phases because they have different color appearances. The bainite phase is shown in bluish color, while the martensite phase is shown in brownish color. Furthermore, the influence of variation in austempering temperature and quench media on microstructure morphology was also discussed. In addition, the calculation of the lattice parameters of the X-Ray Diffraction (XRD) pattern was also carried out in this study to identify the crystal structure formed.